Decrease in aggressiveness in elementary students: The "Strengthening" program - García García, Eddy Eugenio (2020)
The objective was to determine the significant influence of the “Strengthening Me” program on the level of aggressiveness. The sample consisted of students from a school ofComas, aged between 10 and 11 years. The Buss and Perry Aggression Questionnaire (1992, adaptation to the Peruvian reality of Matalinares et al, 2002) was used as an instrument. A quasi-experimental design was planned, in the pretest the results were similar both in the control group and in the experimental group (average and high levels, respectively). In the posttest the results were different: the control group maintained its initial level, but the experimental group reduced its level of aggressiveness.The statistical results obtained (Z = 5.957> 1.6706 and p = 0.000 <0.05) allow us to affirm that the application of the “Strengthening Me” program did have a significant influence on the decrease in aggressiveness, and in its dimensions physical aggressiveness, verbal aggressiveness, anger and hostility.